Factors influencing customers to choose Ar Rahnu in Bank Rakyat Sungai Buloh / Siti Nur Fashah Roslan - Roslan, Siti Nur Fashah (2011)
Ar Rahnu is the most popular tools or mechanism in helping people who are from the middle and the lower income range. In addition, the level of the acceptance of the people toward Ar Rahnu shows an increase from time to times. From this reason, one study is conducted with the aim to identify the factors influence customers to choose Ar Rahnu in Bank Rakyat Sungai Buloh since the numbers of customers do Ar Rahnu in Bank Rakyat increases from year to year. There are seven factors that have been studied, which were liquidity, process, low of safekeeping fees, payback period, safety, Islamic concern and asset pledge. Questionnaire has been used in this study to identify the factors that influence the customers to do Ar Rahnu in Bank Rakyat Sungai Buloh. The researcher chooses to use descriptive research design as method and the researcher use survey in order to collect the data. Data used in this research are primary and so on secondary data such as journal and books. Researcher also use questionnaire to obtain the data in order to get the feedback from customers who applied Ar Rahnu in Bank Rakyat. The sample size in this research is 50 respondents of customers who do Ar Rahnu in Bank Rakyat. The researcher is also able to give some recommendations and suggestion on how to improve and increase the level of customers’ service based on the factor obtained after analysis, findings and interpretation. The conclusion of this study was the outcome from the survey analysis and findings.